The pharmacological potential of sappan wood (Caesalpinia sappan L.): A review of recent evidence - Wirawati, Kadek Tania; Ompusunggu, Gabrios Bonauli; Wardani, Luh; Yanti, Kadek Rahayu Darma (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Sappan wood (Caesalpinia sappan L.) has been used in traditional Asian medicine for centuries, but its pharmacological properties have only recently been systematically investigated using modern scientific methods. This review aims to synthesize current research on the pharmacological activities of sappan wood and assess its potential for development into evidence-based therapeutic applications. A systematic literature search following PRISMA 2020 guidelines was conducted in ScienceDirect and PubMed databases using specific keywords. Articles published between 2014-2024 investigating the pharmacological properties of sappan wood were included, yielding nine studies for qualitative analysis. Evidence demonstrates that sappan wood possesses significant anti-inflammatory, antibacterial, antioxidant, wound healing, antidiabetic, and anti-HIV properties. Brazilin emerges as a key bioactive compound, though synergistic effects among multiple constituents enhance certain activities. Multiple mechanisms of action were identified, including inhibition of pro-inflammatory cytokines, antibacterial effects against both Gram-positive and Gram-negative bacteria, and activation of antioxidant pathways. Sappan wood shows promising potential as a source of natural pharmacological agents with diverse therapeutic applications. Future research should focus on clinical validation, standardization of extracts, and elucidation of molecular mechanisms to facilitate its integration into modern healthcare.